2021
DOI: 10.3390/f12080994
|View full text |Cite
|
Sign up to set email alerts
|

Soil Temperature in Disturbed Ecosystems of Central Siberia: Remote Sensing Data and Numerical Simulation

Abstract: We investigated changes in the temperature regime of post-fire and post-technogenic cryogenic soils of Central Siberia using remote sensing data and results of numerical simulation. We have selected the time series of satellite data for two variants of plots with disturbed vegetation and on-ground cover: natural ecosystems of post-fire plots and post-technogenic plots with reclamation as well as dumps without reclamation. Surface thermal anomalies and temperature in soil horizons were evaluated from remote dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…It was found that after the fire, the value of the NDVI indicator decreases by up to 75% relative to the norm (undisturbed adjacent areas). This is consistent with the results of studies for other objects [13,14]. An additional characteristic was obtained based on the results of processing NDWI data, which characterizes the degree of moisture availability of sites.…”
Section: Resultssupporting
confidence: 91%
“…It was found that after the fire, the value of the NDVI indicator decreases by up to 75% relative to the norm (undisturbed adjacent areas). This is consistent with the results of studies for other objects [13,14]. An additional characteristic was obtained based on the results of processing NDWI data, which characterizes the degree of moisture availability of sites.…”
Section: Resultssupporting
confidence: 91%
“…: [25,59]). Fast-increasing economic activity in cold regions is also impacted by climate change [14,51,46,2,23,50,24], and may generate itself important impacts on permafrost at local scale [57,47,33]. Overall the evolution of permafrost in changing environmental conditions is of primary importance [38].…”
Section: Introductionmentioning
confidence: 99%
“…Satellite data are important for determining the degree of forest disturbance [8,9], for calculating direct fire emissions [10], monitoring the post-fire state of soils [11,12], and vegetation cover and their restoration [13,14]. Of particular interest is the problem of identifying post-fire mortality and restoration of tree stands.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a method for detecting the stage of restoration of vegetation cover in areas after natural, anthropogenic, or human-made impacts by analyzing temperature anomalies of the underlying surface based on satellite imagery in the thermal IR spectral range [12,20].…”
Section: Introductionmentioning
confidence: 99%